The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1183/16000617.0010-2021
|View full text |Cite
|
Sign up to set email alerts
|

Liposomal drug delivery to manage nontuberculous mycobacterial pulmonary disease and other chronic lung infections

Abstract: Nontuberculous mycobacterial (NTM) pulmonary disease is a chronic respiratory infection associated with declining lung function, radiological deterioration and significantly increased morbidity and mortality. Patients often have underlying lung conditions, particularly bronchiectasis and COPD. NTM pulmonary disease is difficult to treat because mycobacteria can evade host defences and antimicrobial therapy through extracellular persistence in biofilms and sequestration into macrophages. Management of NTM pulmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 148 publications
0
12
0
Order By: Relevance
“…S7A). Recent studies have indicated that liposomes are widely used as drug carriers owing to their safety and ability to transport agents to target sites [ 14 ]. The prepared liposomes showed a 88% entrapment efficiency for loading ZNF416 siRNA with a zeta potential of 34.65 mV and hydrodynamic diameter of 146 nm (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S7A). Recent studies have indicated that liposomes are widely used as drug carriers owing to their safety and ability to transport agents to target sites [ 14 ]. The prepared liposomes showed a 88% entrapment efficiency for loading ZNF416 siRNA with a zeta potential of 34.65 mV and hydrodynamic diameter of 146 nm (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…One possible route is the creation of an MS-40S/MS-40-loaded liposome, as has been shown with rifampicin in the treatment of pulmonary Mycobacterium abscessus infections [ 54 ]. Creating an aerosolized antimicrobial therapy would also allow us to achieve higher concentrations of the drug, and increase lung penetration, which is especially important for CF pulmonary infections [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…NTM are ubiquitous in the environment, rendering avoidance impossible [ 53 ]. Typically, NTM infection arises from inhalation of contaminated environmental particles such as aerosols and dust or aspiration of contaminated substances [ 18 , 40 , 50 ]. In the environment, biofilms containing NTM can be found in water distribution systems, while examples of intracellular niches include amoeba in water [ 54 , 55 ].…”
Section: Methodsmentioning
confidence: 99%
“…Many factors contribute to the challenges of treating NTM-PD; these include characteristics of the non-tuberculous mycobacteria (NTM) species and its intrinsic resistance capabilities [ 16 , 17 ] as well as the ability of NTM to evade host defences through sequestration in biofilms and macrophages in the lung, making effective antibiotic penetration and treatment difficult [ 18 ]. In addition, symptoms of NTM-PD are non-specific and mirror those of underlying conditions, and diagnosis is often delayed for a number of years for some patients who have moderate-to-severe symptoms at the time of diagnosis [ 19 21 ].…”
Section: Introductionmentioning
confidence: 99%